1995
DOI: 10.1074/jbc.270.19.11437
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of Actin Filaments Derived from Thermal Fluctuations

Abstract: Single actin filaments undergoing brownian movement in two dimensions were observed at 20 degrees C in fluorescence optical video microscopy. The persistence length (Lp) was derived from the analysis of either the cosine correlation function or the average transverse fluctuations of a series of recorded shapes of filaments assembled from rhodamine-action. Phalloidin-stabilized filaments had a persistence length of 18 +/- 1 micron, in agreement with recent observations. In the absence of phalloidin, rhodamine-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
413
9
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(488 citation statements)
references
References 73 publications
55
413
9
2
Order By: Relevance
“…3 Cofilin lowers the persistence length of actin filaments ∼5-fold ( Table 1). The persistence length of native actin filaments (without phalloidin) under our experimental conditions is 9.8 ±0.1 µm (Table1); comparable to a previously reported value of 9.0±0.5 µm measured under slightly different buffer conditions, 19 and the value predicted from molecular dynamics simulations. [20][21][22] 23 and vimentin 24,25 ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…3 Cofilin lowers the persistence length of actin filaments ∼5-fold ( Table 1). The persistence length of native actin filaments (without phalloidin) under our experimental conditions is 9.8 ±0.1 µm (Table1); comparable to a previously reported value of 9.0±0.5 µm measured under slightly different buffer conditions, 19 and the value predicted from molecular dynamics simulations. [20][21][22] 23 and vimentin 24,25 ).…”
Section: Resultssupporting
confidence: 75%
“…contour length of a segment) over which correlation between the corresponding tangent angles (θ(s)) of a fluctuating semi-flexible polymer, such as an actin filament, are lost in three-dimensional space. 17,18 The average cosine correlation function (〈C(s)〉) defines the L p -dependence of tangent angle (θ) correlation of any segment (arc) length (s) along the contour length (L) of a filament constrained to two-dimensional motion within a plane according to 19 :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this aim, we first characterized the effect of phalloidin and nucleotide analogues separately. Our experiments showed that the binding of ADP.BeF x , ADP.AlF 4 , or phalloidin stabilized the structure of actin filaments, in agreement with previous studies (37,38). In the presence of 3 mM BeSO 4 and 10 mM NaF, the T m was greater (84.8 °C) than in the absence of them (64.1 °C) (Figure 2A Figure 2B).…”
supporting
confidence: 81%
“…However, this does not exclude the possibility that cooperativity occurs across rather than along the actin filament. To test this, we added phalloidin, which binds near the thin filament axis with an orientation that is invariant with thin filament conformation (22) and both decreases thin filament flexibility and alters strand-strand interactions (23)(24)(25). Any cooperativity that was dependent upon such interactions might be changed by the addition of phalloidin.…”
Section: Relationship Between Ca 2ϩ Binding To the Thin Filament Regumentioning
confidence: 99%